Prehospital Pediatric Care: Opportunities for Training, Treatment, and Research. (3rd July 2015) - Drayna, Patrick C.; Browne, Lorin R.; Guse, Clare E.; Brousseau, David C.; Lerner, E. Brooke
Abstract Objective. Pediatric transports comprise approximately 10% of emergency medical services (EMS) requests for aid, but little is known about the clinical characteristics of pediatric EMS patients and the interventions they receive. Our objective was to describe the pediatric prehospital patient cohort in a large metropolitan EMS system. Methods. This retrospective analysis of all pediatric (age <19 years) EMS patients transported from October 2011 to September 2013 was conducted by reviewing a system-wide National EMS Information System (NEMSIS)-compliant database of all EMS patient encounters. We identified the most common primary working assessments, the frequency of abnormal initial vital signs, and the interventions provided. Vital signs included systolic blood pressure (SBP), respiratory (RR) and pulse rate, Glasgow Coma Scale (GCS), pulse oximetry (Pox), and respiratory effort. We defined abnormal vital signs using previously reported age-specific standards. We identified the working assessments most frequently associated with abnormal vital signs and the working assessments associated with the most commonly performed interventions. Data were analyzed using descriptive statistics. Results. There were 9, 956 pediatric transports, 8.7% of the total call volume. The most common working assessments were "other" (16.1%), respiratory distress (13.7%), seizure (12.4%), and blunt trauma (12.0%). Vital signs were documented at variable rates: RR (91.1%), GCS (82.9%), SBP (71.3%), pulse (69.4%), respiratory effort (49.7%), and Pox (33.5%). Of all transported patients, 61.5% had a documented abnormal initial vital sign. Patients with an abnormal vital sign had the same most common working assessments as those with normal vital signs. Glucometry (16.9%), medication delivery (13.6%), and IV placement (11.5%) were the most common interventions and were most often provided to patients with working assessments of seizure, asthma, trauma, altered consciousness, or "other." Cardiopulmonary resuscitation (0.4%), bag mask ventilation (0.4%), and advanced airway (0.4%) occurred rarely and were most often performed for cardiac arrest and trauma. Conclusions. Children made up a small part of EMS providers' clinical practice; those encountered most frequently had respiratory distress, seizures, trauma, or an undefined assessment (i.e., "other"). EMS providers frequently encounter children with physiologic evidence of acute illness, although vital sign documentation was incomplete. Prehospital providers infrequently perform pediatric interventions. Describing EMS providers' interaction with children provides the opportunity to target improvements in pediatric prehospital treatment, training, and research.